Preparation and application of MoS2-based composite film resistant to humid environment and good in humid and hot storage stability

By depositing Ti transition layer and MoS2-Ti-CeO2 layer on the MoS2-based film, the film density is improved by using the solid solution form of Ti and CeO2, which solves the problem of degradation of friction performance of MoS2-based film after storage in a humid and hot environment, and achieves the effect of excellent vacuum tribological performance after long-term storage in a humid and hot environment.

CN119736590AActive Publication Date: 2025-04-01LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411857829.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-01
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

After the existing MoS2-based film is stored in a humid and hot environment for a long time, its vacuum tribological performance has dropped sharply, making it difficult to serve in space for a long time.

Method used

The closed-field non-equilibrium magnetron sputtering technology is used to first deposit the Ti transition layer on the surface of the substrate, and then deposit the MoS2-Ti-CeO2 layer on the Ti transition layer. The denseness and tribological life of the film are improved by the solid solution form of Ti and CeO2.

Benefits of technology

After 2 months of storage in a humid and heat environment (40°C; 90%RH), the average friction coefficient of the MoS2-Ti-CeO2 film is lower than 0.02 and the friction life is greater than 9×105 revolutions, which significantly improves the moisture and heat storage stability and vacuum tribological properties of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736590A_ABST
    Figure CN119736590A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of solid lubricating films, and mainly relates to preparation and application of a MoS2-based composite film which is resistant to a humid environment and has good humid and hot storage stability. The preparation method of the thin film comprises the following steps: firstly, depositing a Ti transition layer on the surface of a base material by using two Ti targets and two MoS2 / CeO2 composite targets by adopting a closed field unbalanced magnetron sputtering technology; next, the Ti target current is reduced, and the MoS2 / CeO2 composite target current is increased; and the MoS2-Ti-CeO2 composite film deposited on the base material is enabled to have good binding force. The film has the advantages of compact structure, excellent vacuum tribology performance, good humidity and heat resistance and the like. The problem that the tribological performance of the MoS2-based thin film is sharply reduced after the MoS2-based thin film is stored in a humid environment is solved, the multi-environment adaptability of the MoS2-based thin film is improved, and it is guaranteed that a spacecraft reliably serves for an ultra-long time in a space environment after being assembled and stored on the ground.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid lubrication, and in particular to a MoS2-based composite film which is resistant to humid environments and has good wet-heat storage stability and a preparation technology thereof. Background Art

[0002] With the higher requirements for the functional diversity and ultra-long life of spacecraft, higher requirements are also put forward for the adaptability of solid lubricating coatings. During the assembly, launch and transportation of spacecraft, it is inevitable to be exposed to a humid and hot environment for a long time. Among them, the vacuum tribological performance of the film after long-term storage in a humid and hot environment is crucial. During the assembly, transportation and storage in a humid atmosphere, the lubricating materials on the surface of the spacecraft will be corroded and damaged by oxygen and water vapor. Lubricating coatings (such as DLC) films with good tribological properties in the atmosphere are very easy to fail in a high vacuum environment. In contrast, MoS2-based solid lubricating films have excellent tribological properties in a vacuum environment, but their tribological properties in the atmosphere are easily affected by humid air. However, considering that the service time of most spacecraft in space is much longer than the manufacturing and assembly time on the ground, we optimized the structure of MoS2-based films with excellent vacuum tribological properties so that they can still maintain excellent vacuum tribological properties after long-term storage in a humid and hot environment, so as to improve the reliability of the film in long-term service in space.

[0003] In order to improve the structure of MoS2-based films and make them have better environmental adaptability and friction performance, previous researchers usually adopted the method of doping conventional metal elements and their oxides (such as Ni, Cr, Nb, Au, Pb, Cu, Ti, Sb2O3) or preparing multilayer film structures to reduce the impact of the environment on the film. However, during long-term wet and hot storage, the structural density of traditional metal-doped MoS2-based films needs to be improved. Water vapor and oxygen will oxidize along the grain boundaries of the film and quickly destroy the film structure. How to make MoS2-based films still have excellent vacuum tribological properties after long-term storage in a wet and hot environment is a challenge. At this stage, it has become an urgent problem to provide a MoS2-based film and its preparation method that is simple to prepare and can still maintain excellent intrinsic tribological properties after long-term storage in a wet and hot environment. Summary of the invention

[0004] In view of the problems existing in the above-mentioned background technology, the present invention provides a MoS2-based composite film which is resistant to humid environments and has good wet-heat storage stability and a preparation method thereof, so as to ensure that the spacecraft can still serve reliably in space for a long time after being stored in a wet-heat environment.

[0005] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a MoS2-based composite film that is resistant to humid environments and has good wet heat storage stability comprises the following steps: 1) First place the substrate in the vacuum chamber of the magnetron sputtering equipment and maintain the vacuum degree ≤8×10 -5 Pa, and use a cold trap to remove moisture from the chamber; 2) Adopt closed field unbalanced magnetron sputtering technology, use metal Ti target as target material, and inert gas Ar gas as sputtering gas source to deposit Ti transition layer on the surface of substrate; process parameters are as follows: sputtering current of metal Ti target is 2~5A, flow rate of Ar gas is 20~40sccm, and deposition time is 0.2~0.3h; 3) Using Ti target and MoS2 / CeO2 composite target (purchased from Hezong New Materials Co., Ltd.), MoS2-Ti-CeO2 layer was deposited on the basis of Ti transition layer; the process parameters were as follows: the sputtering current of metal Ti target was 0.4~0.8A, the sputtering current of MoS2 / CeO2 composite target was 1~1.5A, the flow rate of Ar gas was 20~40sccm, and the deposition time was 2.5~3.5h.

[0006] In step 1), the substrate is one of 718 nickel alloy and high carbon high chromium steel (9Cr18).

[0007] In step 1), after evacuation, 20-40 sccm of Ar gas is introduced, and the bias voltage is increased from -200V to -500V for 20-30 minutes to perform plasma etching and cleaning on the substrate.

[0008] In steps 2) and 3), the substrate bias voltage during deposition is -300V~-20V, and the duty cycle is 40%~60%.

[0009] The present invention adopts closed-field unbalanced magnetron sputtering technology to prepare the coating, using two Ti targets and two MoS2 / CeO2 composite targets respectively. The preparation method is relatively simple and solves the problem that CeO2, a rare earth compound, is non-conductive and cannot be sputtered independently. Compared with traditional metal-doped MoS2-based films, the density and tribological life of the film are greatly improved, and the sensitivity of the film to humid environments is significantly reduced, which improves the reliability of spacecraft in long-term service in space environments after being stored in humid environments.

[0010] In summary, the present invention provides a MoS2-based composite film that is resistant to humid environments and has good wet-heat storage stability, including a Ti transition layer and a MoS2-Ti-CeO2 layer above the transition layer, wherein the Ti content is 5-10at%, and the CeO2 content is 2-5at%; wherein both Ti and CeO2 enter the film in the form of solid solution. Without affecting the intrinsic tribological properties of the film, the sensitivity of the MoS2-based film to water vapor is reduced, and the vacuum tribological properties of the film after long-term storage in a humid environment are significantly improved. After the MoS2-Ti-CeO2 film was stored in a wet-heat environment (40°C; 90%RH) for 2 months, the average friction coefficient of the film was less than 0.02, and the friction life was greater than 9×10 5 The solution effectively solves the problem of a sharp drop in friction performance of MoS2-based films after storage in a humid environment, improves the multi-environment adaptability of MoS2-based films, and ensures the reliable service of the films in the space environment after long-term storage and assembly. In addition, the film preparation process is simple and has good repeatability, which can be industrialized. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 Graphs showing the hardness and elastic modulus of the MoS2-based composite film prepared in an embodiment of the present invention before and after storage in a hot and humid environment (40°C; 90%RH) for 2 months.

[0012] Figure 2 SEM images of the MoS2-based composite film prepared in an embodiment of the present invention; wherein, a is a cross-sectional SEM image of the composite film before storage, b is a surface SEM image of the composite film before storage, and c is a surface SEM image after storage in a hot and humid environment (40°C; 90% RH) for 2 months.

[0013] Figure 3 Raman spectra of the MoS2-based composite film prepared in an embodiment of the present invention before storage in a hot and humid environment (40°C; 90%RH) and after storage for 2 months.

[0014] Figure 4 It is a vacuum friction coefficient curve of the MoS2-based composite film prepared in an embodiment of the present invention before storage in a hot and humid environment (40°C; 90%RH) and after storage for 2 months. DETAILED DESCRIPTION

[0015] The present invention discloses a MoS2-based composite film resistant to humid environments and having good wet heat storage stability, comprising a Ti transition layer and a MoS2-Ti-CeO2 layer located above the Ti transition layer. The Ti content and Ce content in the composite film are 5-10at% and 2-5at% respectively; In the present invention, the thickness of the Ti layer is preferably 0.1 μm to 0.4 μm, and specifically preferably 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm or 0.4 μm.

[0016] In the present invention, the thickness of the MoS2-Ti-CeO2 layer is preferably 2.5µm to 4µm, and specifically preferably 2.5μm, 3μm, 3.5μm or 4μm.

[0017] The present invention also discloses a method for preparing the above-mentioned MoS2-based composite film which is resistant to humid environments and has good wet heat storage stability, comprising the following steps: (1) In the present invention, the substrate is preferably cleaned before use. First, use petroleum ether to ultrasonically treat for 15 minutes to remove grease on the surface of the film; then use acetone to ultrasonically treat for 15 minutes to remove impurities on the surface of the substrate; finally, use nitrogen to blow dry the surface of the substrate to complete the cleaning. Then put the sample into the chamber and draw the vacuum degree of the chamber to ≤8×10 -5 pa, and use a cold trap to remove moisture in the chamber. In the present invention, the vacuum degree of the low-temperature cold trap after water removal is preferably <6.0×10 -5 Pa, more preferably <3.0×10 - 5 Pa.

[0018] (2) Use Ar before sputtering + The sample surface is cleaned. In the present invention, the Ar + The cleaning bias voltage is preferably -200V to -500V, more preferably -400V; the plasma activation cleaning time is preferably 20min to 30min, more preferably 30min.

[0019] (3) Using a metal Ti target as the target material and Ar gas as the sputtering working gas, a Ti transition layer is deposited on the surface of the substrate. In the present invention, the sputtering current of the Ti target is preferably 2A~5A, more preferably 3A~4A; the bias voltage is preferably -300V~-20V, more preferably -250V~-100V, and further preferably -250V~-200V; the deposition time is preferably 0.2h~0.25h. In the present invention, the number of Ti targets in the magnetron sputtering process is preferably 2.

[0020] (4) Depositing a MoS2-Ti-CeO2 layer on the basis of the above-mentioned Ti transition layer. In the present invention, the sputtering current of the Ti target is preferably 0.4A~0.6A, more preferably 0.4A; the sputtering current of the MoS2 / CeO2 composite target is preferably 1.0A~1.5A, more preferably 1.2A~1.4A; the bias voltage is preferably -40V~-80V, more preferably -40V~-60V; the deposition time is optimized to 4h~5h. A MoS2-Ti-CeO2 layer with a thickness of 3µm~5µm is obtained. The number of Ti targets and MoS2 / CeO2 composite targets in the magnetron sputtering process is preferably 2 respectively.

[0021] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Example 1 An unbalanced magnetron sputtering system equipped with a low-temperature cold trap was used, in which two Ti targets and two MoS2 / CeO2 composite targets were evenly arranged, wherein the CeO2 content in the two MoS2 / CeO2 composite targets was 4wt%.

[0023] (1) After cleaning the parts with anhydrous ethanol, place them in an unbalanced magnetron sputtering vacuum chamber and evacuate to less than 3.0×10 -5 Pa. The low temperature cold trap was started to capture and remove the residual water vapor, and high purity argon gas was introduced at 30 sccm, the bias voltage was -400 V, and the surface of the parts was plasma activated and cleaned for 30 minutes.

[0024] (2) 30 sccm of argon gas was introduced, the sputtering current of the Ti target was adjusted to 4 A, a bias voltage of -80 V was applied to the part, and sputtering deposition was performed on the surface of the part to obtain a Ti layer with a thickness of 200 nm.

[0025] (3) The negative bias voltage was adjusted to -40 V, the Ti target current was adjusted to 0.4 A, and the current of the two MoS2 / CeO2 composite targets was adjusted to 1.2 A. Sputtering deposition was performed on the surface of the Ti layer to form a MoS2-Ti-CeO2 film with a thickness of 3.5 μm, thereby obtaining a MoS2-based composite film that is resistant to humid environments and has good wet-heat storage stability.

[0026] Example 2 According to the method of Example 1, a MoS2-based composite film resistant to humid environment and having good wet heat storage stability is prepared, which is different from Example 1 in that: (1) The CeO2 content in the MoS2 / CeO2 composite target is 2wt%; (2) Step (3) Adjust the negative bias voltage to -40 V, adjust the Ti target current to 0.2 A, and adjust the current of the two MoS2 / CeO2 composite targets to 1 A.

[0027] Example 3 According to the method of Example 1, a MoS2-based composite film resistant to humid environment and having good wet heat storage stability is prepared, which is different from Example 1 in that: (1) The CeO2 content in the MoS2 / CeO2 composite target is 6wt%; (2) Step (3) Adjust the negative bias voltage to -40 V, adjust the Ti target current to 0.6 A, and adjust the current of the two MoS2 / CeO2 composite targets to 1.4 A.

[0028] The product structure characterization and performance evaluation are as follows: Figure 1 The hardness and elastic modulus of the MoS2-Ti-CeO2 composite film resistant to humid environments and having good wet-heat storage stability prepared in Example 1 were measured before and after storage in a wet-heat environment (40°C; 90%RH) for 2 months. From the mechanical properties point of view, the hardness of the film did not increase significantly after being stored in a wet-heat environment for 2 months, indicating that no large amount of oxide was generated.

[0029] Figure 2 These are SEM images of the MoS2-Ti-CeO2 composite film prepared in Example 1 that is resistant to humid environments and has good wet-heat storage stability, wherein a is a cross-sectional SEM image of the composite film, b is a surface SEM image of the composite film, and c is a surface SEM image after storage in a wet-heat environment (40°C; 90% RH) for 2 months. Judging from the cross-sectional and surface structure of the film, the film has no clusters or stratification, and the film structure is uniform and dense, and no obvious oxidation defects appear on the film surface after storage in a wet-heat environment.

[0030] Figure 3 The Raman spectra of the MoS2-Ti-CeO2 composite film that is resistant to humid environments and has good wet-heat storage stability prepared in Example 1 before and after storage for 2 months in a wet-heat environment (40°C; 90%RH). It can be seen from the figure that the MoS2-Ti-CeO2 film is amorphous, and only a small amount of oxide is generated on the surface of the film after 2 months of storage in a wet-heat environment.

[0031] Figure 4 The vacuum friction coefficient curve of the MoS2-based composite film prepared in the embodiment of the present invention before and after storage for 2 months in a hot and humid environment (40°C; 90%RH). Tribological performance test conditions: a vacuum ball-disc friction tester was used, and the vacuum degree was <2×10 -3Pa, the friction pair is a Φ6mm GCr15 steel ball, the contact pressure is 5N, the rotation radius is 8mm, and the rotation speed is 1000r / min. It can be seen from the figure that after the film is stored in a hot and humid environment (40℃; 90%RH) for 2 months, the average friction coefficient of the film is still less than 0.02, and the friction life is greater than 9×10 5 change.

Claims

1. A method for preparing a MoS2-based composite film resistant to humid environments and having good wet and hot storage stability, characterized in that: The following steps are involved: 1) Place the substrate in the vacuum chamber of the magnetron sputtering equipment and keep the vacuum degree ≤8×10 -5 Pa, and use a cold trap to remove moisture from the chamber; 2) Adopt closed field unbalanced magnetron sputtering technology, use metal Ti target as target material, and inert gas Ar gas as sputtering gas source to deposit Ti transition layer on the surface of substrate; process parameters are as follows: sputtering current of metal Ti target is 2~5A, flow rate of Ar gas is 20~40sccm, and deposition time is 0.2~0.3h; 3) Using Ti target and MoS2 / CeO2 composite target, a MoS2-Ti-CeO2 surface layer was deposited on the basis of the Ti transition layer; the process parameters were as follows: the sputtering current of the metal Ti target was 0.4~0.8A, the sputtering current of the MoS2 / CeO2 composite target was 1~1.5A, the flow rate of Ar gas was 20~40sccm, and the deposition time was 2.5~3.5h.

2. A method for preparing a MoS2-based composite film resistant to humid environments and having good wet heat storage stability as claimed in claim 1, characterized in that: In step 1), the substrate is one of 718 nickel alloy and high carbon high chromium steel 9Cr18.

3. A method for preparing a MoS2-based composite film resistant to humid environments and having good wet heat storage stability as claimed in claim 1, characterized in that: In step 1), after evacuation, 20-40 sccm of Ar gas is introduced, and the bias voltage is increased from -200V to -500V for 20-30 minutes to perform plasma etching and cleaning on the substrate.

4. A method for preparing a MoS2-based composite film resistant to humid environments and having good wet heat storage stability as claimed in claim 1, characterized in that: In steps 2) and 3), the substrate bias voltage during deposition is -300V~-20V, and the duty cycle is 40%~60%.

5. A MoS2-based composite film prepared by the method as claimed in claim 1, which is resistant to humid environments and has good wet heat storage stability.

6. The MoS2-based composite film resistant to humid environments and having good wet heat storage stability as claimed in claim 5, characterized in that: The MoS2-based composite film includes a Ti transition layer and a MoS2-Ti-CeO2 layer located above the Ti transition layer, and the Ti content and Ce content in the composite film are 5-10at% and 2-5at% respectively.

7. The MoS2-based composite film resistant to humid environments and having good wet heat storage stability as claimed in claim 6, characterized in that: The thickness of the Ti transition layer is 0.1µm-0.4µm, and the thickness of the MoS2-Ti-CeO2 surface layer is 2.5µm-4µm.

8. A MoS2-based composite film prepared by the method of claim 1, which is resistant to humid environments and has good wet-heat storage stability, and is used for friction reduction in space environments.

Citation Information

Patent Citations

  • Use of high temperature superconductive material in antifriction, wear-resistance and lubrication

    CN101121605A

  • Preparation method of molybdenum disulfide compound lubricating film for satellite

    CN107686976A

  • Preparation method of low-friction-coefficient MoS2 base metal-oxide composite solid lubrication film

    CN107841717A

  • MoS2 / YSZ (molybdenum disulfide / yttria stabilized zirconia) composite film with high wear resistance and radiation resistance and preparation method of MoS2 / YSZ composite film

    CN111663110A

  • Method for forming thin film, apparatus for manufacturing thin film, and article having thin film formed thereon

    JP2005272944A